Factors influencing perceived stress among nurses: The case at National Cancer Institute - Kama Azida, Kamarulzaman (2015)
The aim of this study was to investigate the factors influencing perceived stress among nurses; the case at National Cancer Institute (NCI). The independent factors studied are: workload, patient’s death and dying, inadequate preparation, lack of staff support, uncertainty concerning treatment by physician, conflict with physicians and conflict with other nurses. This study examined the level of perceived stress encountered by nurses at the NCI and to identifying the influential among the occupational stressor on nurses at NCI. The Nursing Stress Scale (NSS) by Gray-Toft and Anderson (1981) and the Perceived Stress Scale (PSS) by Cohen et al., (1983) were use as the research instrument. A total of 182 nurses were selected as respondents from a population of 390 nurses. Data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (correlation and multiple regressions). Overall, the findings indicate low level of perceived stress experienced by nurses in NCI. The results of the correlation analysis showed that out of seven factors, six have a low and positive relationship with perceived stress while (uncertainty concerning treatment by physician) shows no relationship at all. Based on multiple regression result study, 19.7% of the perceived stress could be explained by the factors studied. The most influential factors are the inadequate preparation and conflict with physicians factor. This study would like to suggest to the NCI management to initiate proactive measures to address the stress issues exist by providing a range of appropriate on-going training courses that would include techniques of handling stress at work in order to produce productive worker with an excellent work culture